THE EFFECT OF SERVICE MARKETING MIX ELEMENTS ON CUSTOMER-BASED BRAND EQUITY: AN EMPIRICAL STUDY ON â€œsimPATI DISCOVERYâ€ RECIPIENT IN MALANG CITY - Rifai, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This Research aim to examine the Effect of Service Marketing Mix on Customer Based Brand Equity: an Empirical Study on simPATI discovery in Malang City by simultaneous and partially. This Research is explanatory research, in accordance with purpose to describe the casual relationship among variables though hypothesis testing. In this research used 110 samples, the sample and population were the customer simPATI discovery in Malang City. In this research, the data collection method is conducted through questionnaire distribution. The sampling method used purposive sampling. Testing method in this research used Validity Test, Reability test and Classical Assumption Test. Analysis method in this research are multiple regression analysis and hypothesis testing used T test, F test, and dominant test with program SPSS 16. The result of this research showed that by partially analysis used T test can be concluded that product, promotion, physical evidence, and process has significant effect on customer based brand equity and price, place and people by partially didnâ€™t have significant effect on customer based brand equity. Further, the simultaneous analysis used F test can be concluded that variables product, price, place, promotion, people, physical evidence and process together have significant effect on customer based brand equity. The dominant test showed that product is the dominant effect on customer based brand equity. The new fact in this research showed that respondent agreed price, place and people already good enough on simPATI discovery but didnâ€™t make customer based brand equity on simPATI discovery. Â Key Words: Service marketing mix, product, price, place, promotion, people, physical evidence, process, customer based brand equity